Respiratory Syncytial Virus M2-1 Protein Requires Phosphorylation for Efficient Function and Binds Viral RNA during Infection - Cartee, Tara L. (American Society for Microbiology, 2001)
The M2-1 protein of respiratory syncytial (RS) virus is a transcriptional processivity and antitermination factor. The M2-1 protein has a Cys3His1 zinc binding motif which is essential for function, is phosphorylated, and has been shown to interact with the RS virus nucleocapsid (N) protein. In the work reported here, we determined the sites at which the M2-1 protein was phosphorylated and investigated the importance of these phosphorylated residues for M2-1 function in transcription. By combining protease digestion, matrix-assisted laser desorption ionization–time of flight mass spectrometry, and site-directed mutagenesis, we identified the phosphorylated residues as serines 58 and 61, not threonine 56 and serine 58 as previously reported. Serines 58 and 61 and the surrounding amino acids are in a consensus sequence for phosphorylation by casein kinase I. Consistent with this, we showed that the unphosphorylated M2-1 protein synthesized in Escherichia coli could be phosphorylated in vitro by casein kinase I. The effect of eliminating phosphorylation by site-specific mutagenesis of serines 58 and 61 on the function of the M2-1 protein in transcription of RS virus subgenomic replicons was assayed. The activities of the M2-1 protein phosphorylation mutants in transcriptional antitermination were tested over a range of concentrations and were found to be substantially inhibited at all concentrations. The data show that phosphorylation is important for the M2-1 protein function in transcription. However, mutation of the M2-1 phosphorylation sites did not interfere with the ability of the M2-1 protein to interact with the N protein in transfected cells. The interaction of the M2-1 and N proteins in cotransfected cells was found to be sensitive to RNase A, indicating that the M2-1–N protein interaction was mediated via RNA. Furthermore, the M2-1 protein was shown to bind monocistronic and polycistronic RS virus mRNAs during infection.